Roles of agro-nursing in bringing health services in rural and remote areas of Indonesia: Agronursing Services in Rural and Remote Areas - Susanto, Tantut; Berdida, Daniel Joseph E. (Faculty of Nursing Universitas Padjadjaran, 2025)
Agro-nursing is an innovative approach to health care that integrates nursing science with a contextual understanding of agricultural conditions and rural life. Rural and remote areas in Indonesia often face challenges in accessing adequate health care. This article discusses the role of agro-nursing in addressing these challenges, highlighting how nurses can act as agents of change who provide health care and empower communities through approaches appropriate to local characteristics. By utilizing local potential, community culture, and agricultural systems as an integral part of rural life, agro-nursing strengthens health care promotive, preventive, curative, and rehabilitative efforts. This study also highlights the importance of specialized training, cross-sector collaboration, and policy support to optimize the role of agro-nursing in improving the health of communities in remote and disadvantaged areas. It is hoped that agro-nursing can be a sustainable strategy for narrowing the gap in health services between urban and rural areas in Indonesia.